EVALUASI DAMPAK PENERAPAN FAULT DETECTION, ISOLATION AND RESTORATION (FDIR) PADA FEEDER ANDALAS DAN FEEDER ANDURING TERHADAP ENERGY NOT SUPPLIED (ENS) DI PT. PLN (PERSERO) UP2D SUMATERA BARAT - Galuh Aditya; Yusreni Warmi; Andi Syofian (Ensiklopedia of Journal, 2023)
Distribution system outages due to maintenance purpose or 20 kV feeder interruption will emerge undelivered electric energy called with Energy Not Supplied (ENS) in which the ENS amounts is influenced by outage frequencies and durations. ENS suppression efforts through engineering marvels on the Medium Voltage Network (MVN) protection systems and Supervisory Control And Data Acquisition (SCADA) with Fault Detection, Isolation and Restoration (FDIR) scheme by PLN UP2D SUMBAR intended to reduce recovery time duration [1] also minimize outages area during 20 kV feeder interruption.The ENS calculation reckoned according to 20 kV feeder interruption historical data on Feeder Andalas and Feeder Anduring consisting of load and outage duration parameters. Comparison on ENS magnitudes over before and after FDIR implementation will be the evaluation basis of implementation impact. Economic impact significance also compared through rupiah’s nominal loss in accordance of arising ENS magnitude [2].Through FDIR implementation, outage duration during detection and isolation stages on Feeder Andalas decreased up to 5 minutes or 83,33 % hence suppressing the ENS as much as 88.089 kWh worth Rp. 127,262.49 or 73.42 %, while on Feeder Anduring decreased up to 1,07 minutes or 49,23 % hence suppressing the ENS as much as 40,863 kWh worth Rp. 59,034.67 or 52.31% of averages before implementation.